PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATAN EFEKTITAS DI MAS. AL-WASHLIYAH 22 TEMBUNG - Darmansah , Tengku; Istiqomah; M.Kholid pay; Syarifah Tussuriyani HSB (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to determine the role of school principals’ leadership in improving office management effectiveness at Mas Al Washliyah 22 Tembung. The study examines the role of principals in enhancing office management effectiveness in the madrasa. A manager’s leadership plays a crucial role in creating a good business environment, setting vision and goals, and implementing good policies. In this research, qualitative methods and case studies were used in different madrasas. Data were collected through in-depth interviews with principals, teachers, and administrative staff, as well as direct surveys within the madrasa environment. The results of the study show that effective school leaders can motivate and inspire staff, enhance performance, and strengthen internal communication. Visionary leadership and participation in activities have been proven to increase the effectiveness and efficiency of the madrasa. Factors such as a leader’s ability to make effective decisions, resolve conflicts, and create a positive leadership culture also play a role in improving office leaders’ performance. This research concludes that enhancing principals’ leadership skills is crucial in improving madrasa management quality. Recommendations are made for comprehensive and continuous leadership training programs for school leaders to support effective leadership practices in schools.